Why do we need ‘myth-busting’ in the study of Sino–African relations? - Hirono, Miwa; Suzuki, Shogo (Taylor & Francis (Routledge), 2014)
The literature on Sino–African relations has debated whether or not China's growing presence is a threat to Western or African interests, and has come to the conclusion that China's behavior is not uniquely immoral. Many countries, including Western liberal democracies, similarly give aid to local autocrats to secure natural resources. Why, then, has so much effort been made to come to this perhaps unsurprising conclusion? We argue that the literature on Chinese foreign policy remains heavily influenced by Western states' policy interests, resulting in an impoverished debate that is primarily concerned with the idea of a China threat. In order to recover the diversity in our research on Chinese foreign policy, we argue for the need to go beyond the confines of Western strategic interests.